Clinical significance of VEGFR-2 and VEGFR-3 expression in ovarian cancer patients - Klasa-Mazurkiewicz, Dagmara; Jarząb, Mirosław; Milczek, Tomasz; Lipińska, Barbara; Emerich, Janusz (Polish Journal of Pathology, 2011)
The vascular endothelial growth factor (VEGF) family and VEGF receptors (VEGFR) play an essential role in angiogenesis and lymphangiogenesis. The aim of this study was to clarify the prognostic significance of VEGFR expression in ovarian carcinoma. Levels of VEGFR-2 and VEGFR-3 tissue expression in human ovarian tumours were assayed by immunoblotting and the correlations between analysed factors and clinicopathological features were examined. Tissue samples consisted of 42 benign and 10 borderline (low malignant potential – LMP) tumours, 76 ovarian carcinomas, 8 Krukenberg tumours and 32 normal ovarian tissues. The highest relative level of VEGFR-2 was detected in cases with at the early stages of cancer development. The highest level of VEGFR-3 was detected advanced cancer stages and those with Krukenberg tumours. Overexpression of VEGFR-3 was found to correlate with the debulking status (p = 0.02) and positive response to chemotherapy (p = 0.04). A statistically significant longer progression free survival (PFS) was observed in women with a low than with a high expression of VEGFR-3 (p = 0.01). Increased levels of VEGFR-2 expression at the early stages of ovarian cancer may indicate the significance of neoangiogenesis at these stages. Overexpression of VEGFR-3 reflects the aggressiveness of ovarian carcinoma spread and has a predictive value for identifying high-risk patients with poor prognosis.